Enteric-coated mycophenolate sodium in the treatment of non-infectious intermediate uveitis: results of a prospective, controlled, randomised, open-label, early terminated multicentre trial. Issue 5 (13th September 2017) - Deuter, Christoph M E; Engelmann, Katrin; Heiligenhaus, Arnd; Lanzl, Ines; Mackensen, Friederike; Ness, Thomas; Pleyer, Uwe; Stuebiger, Nicole; Wilhelm, Barbara; Luedtke, Holger; Zierhut, Manfred; Doycheva, Deshka
Abstract : Background/aims: To evaluate the efficacy, safety and tolerability of enteric-coated mycophenolate sodium (EC-MPS) in combination with low-dose corticosteroids compared with a monotherapy with low-dose corticosteroids in subjects with non-infectious intermediate uveitis (IU). Methods: Open-label, prospective, controlled, randomised multicentre trial. Patients were randomised in a 1:1 ratio to either the treatment group (prednisolone plus EC-MPS) or control group (prednisolone monotherapy). Patients in the control group who relapsed within 6 months changed to the crossover group (prednisolone plus EC-MPS). Maximum treatment duration was 15 months. The primary endpoint was the time to first relapse in the treatment group and control group. Results: Forty-one patients at eight sites were analysed. Twenty-two patients were allocated to the treatment group, with 19 patients in the control group. A first relapse occurred in 9 patients (40.9%) in the treatment group and 15 patients (78.9%) in the control group (p=0.03). The median time to the first relapse was >15 months for the treatment group and 2.8 months for the control group (p=0.07). The probability of relapse-free survival at month 15 was estimated to be 52.9% in the treatment group and 19.7% in the control group (p=0.01). 15 patients changed to the crossover group. Of these, only four patients developed a second relapse. No safety concerns arose during the trial. Only one patient had to discontinue EC-MPS due to increased liver enzymes. Conclusion: EC-MPS can be considered an effective and well-tolerated immunosuppressive drug to prevent relapses in patients with chronic IU. Trial registration number: EUDRACT number: 2009-009998-10, Results.